1993
DOI: 10.1111/j.1442-200x.1993.tb03099.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of pulmonary hemodynamics on manifestation of allergic asthma in patients with congenital heart disease

Abstract: The purpose of this study was to determine whether pulmonary hemodynamic abnormalities relate to manifestations of allergic asthma. In 448 patients with congenital heart disease the relationships between asthma and age or pulmonary arterial blood (PA) flow were studied. Asthma (allergic and non‐allergic) was more common in 39 (19%) of 201 patients with high PA flow, compared with the incidence in those with normal PA flow (6/117, 5%; P < 0.001) and reduced PA flow (1/130, 1%; P < 0.05). In the high PA flow gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Other workers have highlighted the role of pulmonary hypertension in some of the patients presenting with asthma-like symptoms. Some cases of pulmonary arterial hypertension (PAH) have been misdiagnosed as asthma, and some of the reports of CHD co-existing with asthma were in patients who also had pulmonary hypertension 4,8,10. VSD and several other CHD are often associated with PAH, and our 2 patients are also likely to have had PAH since they both had large VSD.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Other workers have highlighted the role of pulmonary hypertension in some of the patients presenting with asthma-like symptoms. Some cases of pulmonary arterial hypertension (PAH) have been misdiagnosed as asthma, and some of the reports of CHD co-existing with asthma were in patients who also had pulmonary hypertension 4,8,10. VSD and several other CHD are often associated with PAH, and our 2 patients are also likely to have had PAH since they both had large VSD.…”
Section: Discussionmentioning
confidence: 74%
“…Infact, congenital cardiovascular anomalies are believed to be significantly associated with congenital and acquired airway disorders 2. Although the prevalence of asthma and/or airway hyper-responsiveness (AHR) in children with CHD is not known, some authors have suggested that asthma or AHR is more common in children with CHD than in the general population 58. Tsubata and co-workers reported that 6 out of 10 of their patients with congestive heart failure (CHF) secondary to CHD had AHR elicited by histamine challenge,5 while Ackerman et al identified an extremely strong association between a particular CHD (pulmonary atresia with VSD) and persistent AHR.…”
Section: Introductionmentioning
confidence: 99%
“…Tsubata and coworkers [12] reported that 6 out of 10 of their patients with congestive heart failure (CHF) secondary to CHD had AHR elicited by histamine challenge, while Ackerman et al [8] identified an extremely strong association between pulmonary atresia with VSD and persistent AHR. Matsuoka et al have suggested that pulmonary congestion in infancy may increase the risk of atopic asthma in genetically predisposed children [13,15]. For clinicians practicing in a developing country, the clinical significance of the co-existence of these two conditions may lie mainly in the fact that both could present in a similar manner, since many CHD as well as asthma, present chiefly with respiratory distress.…”
Section: Discussionmentioning
confidence: 94%
“…Although the prevalence of asthma and/or airway hyper-responsiveness (AHR) in children with Fig. 2 Chest radiograph showing bilateral hyperinflated lung fields, flattened domes of diaphragm with normal cardiac silhouette CHD is not known, some authors have suggested that asthma or AHR is more common in children with CHD than in the general population [12][13][14][15]. Tsubata and coworkers [12] reported that 6 out of 10 of their patients with congestive heart failure (CHF) secondary to CHD had AHR elicited by histamine challenge, while Ackerman et al [8] identified an extremely strong association between pulmonary atresia with VSD and persistent AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly such patients have a left-to-right shunt, increased pulmonary blood flow, and pulmonary hypertension that results in low pulmonary compliance. 3,18 Resistance to pulmonary infection may be reduced in this setting. 19 Although our patient did not undergo cardiac catheterization to prove the hemodynamic basis for his symptoms, it is quite likely that he had some degree of pulmonary venous hypertension secondary to the small opening between the accessory chamber and the lower portion of the left atrium.…”
Section: Discussionmentioning
confidence: 99%